Institutional features of regulation of non-standard employment in Kazakhstan (Journal of Economic Research & Business Administration, 2018)
The employment problem acquires the character of flexibility under the influence of the adaptationof the market economy, transforming into various forms of employment. Non-standard forms ofemployment have become the total definition of this phenomenon. This term is already consistentlyentered into the era of post-industrial economy in developed countries in the 1970s. Under theinfluence of constantly changing conditions, the post-industrial era issues new labor relations. Thisarticle is devoted to the nonstandard employment of Kazakhstan. There are legal regulation, legislativeaspects: independent, distance, home, temporary employment and work of disabled people(working hours). The issues of productive and unproductive employment are covered. The articleexamines the peculiarities of the legislation about employment protection, where considers the balanceof labor protection rigidity, and the degree of flexibility of labor legislation, thus, the balanceof labor laws determines the number of unemployed who, in turn, lead to non-standard forms ofemployment. Examined utterance of self-employment in Kazakhstan and the different approach ofstate bodies to this phenomenon. The aspects of social insurance and granting of benefits for loss ofwork in the Republic of Kazakhstan were studied. Legislative moments of registration of individualentrepreneurship have been studied. The procedure for registering the unemployed in the employmentcenter. Foreign experience It is given mainly in Germany, where questions of employment ofelderly people on non-permanent work are covered. The study of non-standard forms of employmentis limited to surface assessments, which are largely due to the diversity of forms of employment,therefore it is required to improve the methodological basis for determining the scope of thisphenomenon and his dynamics.